DORONGAN BELAJAR SISWA PASCA PEMBERIAN BOS Studi Etnografi di SD Negeri Batursari 1 Kecamatan Mranggen Kabupaten Demak - Mulyani, Mulyani (2010)
Research's focus is how is the studying pushing students after giving BOS. Purpose of research is to (1) to know the studying pushing students at District Elementary School Batursari 1 Mranggen, Demak after giving BOS, (2) to know the role of teachers in giving studying pushing students at District Elementary School Batursari 1 Mranggen, Demak after giving BOS, and (3) to know studying result of student at District Elementary School Batursari 1 Mranggen Demak after giving BOS. This is the type of qualitative research. This research was conducted in a District Elementary School Batursari 1 Mranggen Demak regency. The main subject of research is the principal and teachers. Techniques of data collection using interviews, observation, and documentation. Data analysis techniques in a single site that is District Elementary School Batursari 1 starts from Demak district to build grain, enter data and analyze data. Test the validity of the data using the credibility, tranferabilitas, confirmability and dependability. Research's result is (1) the student motivation in studying at District Elementary School Batursari 1 Mranggen, Demak after giving BOS is done by carry on learning book for every student. Because of that the student did not faced any problem in studying. So that studying pushing is still kept. Studying pushing form students at District Elementary School Batursari 1 Mranggen, Demak is additional lesson activity, computer extracurricular, visiting library activity and learning activity in the class. The stdying pushing students after giving BOS is shown by student participation to follow additional lesson activity. Student is interested when teacher is conveying the material with learning media which is from BOS fund. Student also takes participation in computer extracurricular because it can show the moving picture. (2) The role of teachers studying pushing students at District Elementary School Batursari 1 Mranggen, Demak after giving BOS are helped in learning media and learning source, as a result from BOS fund allocation. It mean that BOS fund has been allocated to buying books and learning media can help the teacher in teaching learning activity. (3) The studying result of student at District Elementary School Batursari 1 Mranggen Demak after giving BOS is shown by the increasing of average value of lesson in last 5 years, 60% graduation can accept in SMP N. Those studying result can be better because BOS support is become important factor in teaching learning activity at school so that it can affect the student learning result.